Rapid evidence profile #59: Examining the views and experiences of workplace-injury remediation and its impact on return-to-work timelines - Grewal, E; Waddell, K; Wilson, MG (My University, 2023)
An overview of the best available research evidence from around the world (i.e., evidence syntheses) and local research evidence (i.e., single studies) and may include a scan of experiences from other countries and from Canadian provinces and territories, about the views and experiences of workplace-injury remediation and its impact on return-to-work timelines in response to a decision-maker’s request.
Keywords: workplace-injury; remediation; return-to-work